Career Readiness in Adolescents: A Systematic Literature Review (SLR) Approach - Retna Sukmadiningsih; Dede Rahmat Hidayat; Eka Wahyuni (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to conduct a systematic review of the literature discussing career readiness in adolescents, focusing on nine primary articles published between 2020 and 2024. This study uses the PRISMA approach to select and analyze articles from scientific databases, namely Google Scholar and Semantic Scholar. Inclusion criteria include peer-reviewed articles, relevant to the context of career readiness in adolescents, and presenting significant empirical and conceptual findings. The nine articles analyzed raise various approaches to improving readiness, such as school-based career guidance interventions, entrepreneurship education that develops students' mindset and growth mindset, and the use of technology in synchronous online learning. In addition, the study also includes a conceptual review and development of assessment instruments based on a multidimensional approach. The findings show that career readiness is a complex construct influenced by internal factors such as self-efficacy, metacognition, and goal orientation, and is influenced by contextual learning approaches and systemic support from schools. This study provides important insights into the design of evidence-based career guidance programs, the development of more accurate and holistic readiness assessment instruments, and highlights the urgency of synergy between pedagogical approaches and future-oriented career readiness.